Effect of gamma irradiation on silica-enriched biochar and biofertilizer on the productivity of rice grown on degraded Latosol soil - Robifahmi, Nur; Hanani, Muftia; Bachtiar, Taufiq; Flatian, Anggi Nico; Slamet, Sudono; Citraresmini, Ania (Journal of Degraded and Mining Lands Management, 2025)
The degraded Latosol soil is characterized by its acidity and low organic matter content, which limits rice productivity. Improving the chemical properties of the soil is crucial for supporting the sustainability of paddy fields. This study aimed to enhance these properties using silica-enriched biochar through gamma irradiation as a biofertilizer carrier. Rice husk biochar was selected for its resistance to decomposition and was enriched with SiO? to fulfill the nutritional needs of rice plants. The treatments tested were combinations of biochar-silica formulas (F0 = no formula, F1 = biochar-silica with rice husk ash, and F2 = biochar-silica with zeolite) and NPK fertilizer doses (R0 = no fertilizer, R1 = 50% recommended dose, R2 = 100% recommended dose). The results showed that the F1 formula combined with the full NPK dose (R2) significantly improved soil structure, increased organic carbon content, and enhanced nutrient uptake efficiency, which in turn, promoted higher rice productivity. The use of silica-enriched biochar as a carrier for biofertilizers has proven effective in supporting the sustainability of paddy soils. The F1 formula with a full dose of NPK can be recommended to enhance rice productivity while maintaining soil fertility.